Expressed Sequence Tags Analysis and Design of Simple Sequence Repeats Markers from a Full-Length cDNA Library in Perilla frutescens (L.) - Eun Soo Seong; Ji Hye Yoo; Jae Hoo Choi; Chang Heum Kim; Mi Ran Jeon; Byeong Ju Kang; Jae Geun Lee; Seon Kang Choi; Bimal Kumar Ghimire; Chang Yeon Yu (International Journal of Genomics)
Perilla frutescens is valuable as a medicinal plant as well as a natural medicine and functional food. However, comparative genomics analyses of P. frutescens are limited due to a lack of gene annotations and characterization. A full-length cDNA library from P. frutescens leaves was constructed to identify functional gene clusters and probable EST-SSR markers via analysis of 1,056 expressed sequence tags. Unigene assembly was performed using basic local alignment search tool (BLAST) homology searches and annotated Gene Ontology (GO). A total of 18 simple sequence repeats (SSRs) were designed as primer pairs. This study is the first to report comparative genomics and EST-SSR markers from P. frutescens will help gene discovery and provide an important source for functional genomics and molecular genetic research in this interesting medicinal plant.